Prevalence of HLA DQB1*0602 allele in patients with migraine Prevalência do alelo HLA DQB1*0602 em pacientes com enxaqueca - Fernando Morgadinho Santos Coelho; Márcia Pradella-Hallinan; Paulo Corrêa Abud; Mario Predazzoli Neto; Fabio Moreira; Lia Rita Azeredo Bittencourt; Mario Fernandes Pietro Peres; Sérgio Tufik (Arquivos de Neuro-Psiquiatria, 2007)
BACKGROUND: Studies have shown a high prevalence of migraine among narcoleptic patients. HLA-DQB1*0602 and HLA DRB1 alleles are closely associated with narcolepsy. An increase in the HLA-DRB1 allele frequency in patients with visual aura has raised greater awareness of the genetic background in migraine. PURPOSE: Since the regions DR and DQ of the HLA are in tightly linkage desiquilibrium we hypothesize that HLA-DQB1*0602 might be associated to the pathophysiology of migraine. METHOD: We analyzed the presence of HLA DQB1*0602 allele in 50 healthy subjects with no history of migraine, 53 patients with migraine without aura and 52 patients with migraine with aura. RESULTS: There was no difference in the frequency of HLA DQB1*0602 allele when control subjects and all patients were compared. We failed to note any difference in frequencies when comparing migraine patients with and without aura. CONCLUSION: Further studies with different patient populations, with other hypothalamic markers (melatonin, hypocretin) in migraine patients may shed light on to its pathophysiology. CONTEXTO: Estudos têm demonstrado o aumento da prevalência de enxaqueca em pacientes com narcolepsia, um distúrbio de sono associado a um gene do sistema HLA, o alelo HLA-DQB1*0602. As regiões DQ e DR do HLA estão em alto desequilíbrio de ligação e já foi descrito um aumento da freqüência do alelo HLA DRB1 em pacientes com enxaqueca com aura visual, o que fortalece uma hipótese de herança genética para a enxaqueca. OBJETIVO: Nossa hipótese é que o alelo HLA-DQB1*0602 pode estar relacionado com a fisiopatologia da enxaqueca destes pacientes. MÉTODO: Nós analisamos a presença do alelo HLA-DQB1*0602 em 50 voluntários sadios sem história de enxaqueca, 53 pacientes com enxaqueca sem aura e 52 pacientes com aura. RESULTADOS: Não houve diferença entre os controles sadios e os pacientes com enxaqueca. Não houve diferença entre os pacientes com enxaqueca com e sem aura. CONCLUSÃO: Futuros estudos com diferentes populações, com outros marcadores (melatonina e hipocretina) em pacientes com enxaqueca devem ser realizados para melhor esclarecimento de fisiopatologia.